2008
DOI: 10.1080/10503300701810793
|View full text |Cite
|
Sign up to set email alerts
|

Treatment failure in psychotherapy: The pull of hostility

Abstract: Client-therapist interactions were studied in 14 positive-change (PC) and 14 negative-change or nonchange (NC) therapies with the same therapists and similar clients. Aggregated structural analysis of social behavior (SASB) scores showed increasingly dissimilar interaction styles between client and therapist in NC therapies. First-lag transition analyses of SASB codings of Sessions 3, 12, and 20 showed the following differences: Stable hostile complementarity characterized NC within and across sessions. Hostil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 31 publications
7
46
0
3
Order By: Relevance
“…Research on outcome prediction, treatment dropout and patient-therapist interaction supports the importance of measuring SASB self-image variables in ED (e.g. Birgegård, Björck, Norring, Sohlberg, & Clinton, 2009;Björck, Clinton, Sohlberg, & Norring, 2007Von der Lippe, Monsen, Rønnestad, & Eilertsen, 2008).…”
Section: Structural Analysis Of Social Behaviour (Sasb)mentioning
confidence: 95%
“…Research on outcome prediction, treatment dropout and patient-therapist interaction supports the importance of measuring SASB self-image variables in ED (e.g. Birgegård, Björck, Norring, Sohlberg, & Clinton, 2009;Björck, Clinton, Sohlberg, & Norring, 2007Von der Lippe, Monsen, Rønnestad, & Eilertsen, 2008).…”
Section: Structural Analysis Of Social Behaviour (Sasb)mentioning
confidence: 95%
“…Lack of management of counter‐transference reactions and therapist misunderstanding of the patients' problems or needs can lead to poor working alliance (Gelso & Hayes, 2007; Hayes et al , 1998; Rhodes, Hill, Thompson, & Elliott, 1994). Von der Lippe, Monsen, Rønnestad, and Eilertsen (2008) reported from their study of 28 psychotherapy processes where 14 had poor outcome. They found that the therapist–patient interaction in the negative outcome group was characterized by a growing complementary hostility, and that level of hostility in session 12 predicted the poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…En vedvarende avvisning av å anerkjenne terapeutens kompetanse gjorde trolig denne mer utsatt for å reagere med mer eller mindre subtil fiendtlighet og avvisning tilbake. Dette ble antatt å vaere hovedårsa-ken til det dårlige utfallet for disse pasientene (17).…”
Section: Eksempler Fra Forskningenunclassified